PERENCANAAN LABA DENGAN TITIK IMPAS SEBAGAI DASAR PENGAMBILAN KEPUTUSAN BAGI PIHAK PENGELOLA CV. RANDU SARI SATU - Andrian Anwar L Nata; Novi Riani; Abshor Marantika; Epid Apriani (Derivatif : Jurnal Manajemen, 2021)
CV. Randu Sari Satu is a place of business that produces various types of mattresses, pillows and bolsters made of cotton. So far, in running its business, CV. Randu Sari Satu costs not yet classified as full variable costs or fixed costs. Therefore, this study aims to determine the achievement of the break even point in CV. Randu Sari Satu 2016-2020 and the amount of margin of safety achieved by CV. Randu Sari Satu 2016-2020.The calculation in this study uses the calculation of the level of sales, safety margin analysis, selling price of decision makers, costs and volume of company profits.Based on the results of the analysis, it can be concluded that during 2016-2020, it can be seen that the highest breakeven point is in the year while the lowest breakeven point is in 2020. Meanwhile, the achievement of the highest quantity was in 2020. and the achievement of small quantities in 2016 and 2018. by CV. Randu Sari Satu is good and above the break-even point statistic, so CV. Randu Sari Satu is able to make a profit every year. Margin of Safety describes the distance between planned sales and sales at break-even. It can be seen that the margin of safety also provides information about the distance limit, where if the decline in sales exceeds the distance limit, the CV. Randu Sari Satu will suffer losses. Seeing the results of the calculations that have been dSatu, in 2018 the safety margin achieved by CV. Randu Sari Satu is only 26.9%, the lowest compared to other years. In 2016 CV. Randu Sari Satu is vulnerable to losses, because the smaller the safety margin means the faster CV. Randu Sari Satu suffered a loss. Meanwhile in 2019 the margin of safety was achieved by CV. Randu Sari Satu is only 74.3% which shows the highest value from other years, meaningthat 2019 is in a safe condition.Keywords : Profit Planning, Break Even Point